2014
DOI: 10.5455/msm.2014.26.191-194
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Societal Stigma and Discrimination Towards People Living with HIV/AIDS in Lagos, Nigeria: a Qualitative Study

Abstract: Introduction:The perception of People Living with HIV/AIDS (PLWHAs) on how the public feels about them could influence their willingness to seek medical care, interaction with the society and their coping strategies.Material and methods:This study assessed the perception and behavior of PLWHAs towards societal stigma and discrimination in Lagos, Nigeria. This was a qualitative, descriptive cross sectional study among PLWHAs from three of the three senatorial districts in Lagos State selected using simple rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
(21 reference statements)
1
22
0
Order By: Relevance
“…The major reasons for termination of employment among HIV infected people were psychological one, not physical or symptoms-associated conditions (Vitry-Henry, Pénalba, Beguinot, & Deschamps, 1999). Olalekan, Akintunde & Olatunji (2014) examined stigma and discrimination against PLWHA in Lagos Nigeria. The authors found that PLWHA were depressed because of episodes of stigma and discrimination against their personality in public, family, healthcare and workplace settings.…”
Section: Introductionmentioning
confidence: 99%
“…The major reasons for termination of employment among HIV infected people were psychological one, not physical or symptoms-associated conditions (Vitry-Henry, Pénalba, Beguinot, & Deschamps, 1999). Olalekan, Akintunde & Olatunji (2014) examined stigma and discrimination against PLWHA in Lagos Nigeria. The authors found that PLWHA were depressed because of episodes of stigma and discrimination against their personality in public, family, healthcare and workplace settings.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges include travel distance [14], cost of services [15], unfriendly service hours [16], delay in service provision [17], and unfriendly and stigmatising health care providers [18]. Unfriendly and stigmatising behaviour of health care providers have been especially troublesome for key populations [16].…”
Section: Introductionmentioning
confidence: 99%
“…The loss in significant difference between single and married PLWHA for DS is not unexpected. There is an evidence suggesting that disclosure concerns are inevitable for individuals suffering from chronic illness and PLWHA, whether single or married, are no exception [7,21]. Disclosure is necessary to obtain social support [24], and each new disclosure would risk a stigmatizing response, regardless of how well past disclosure experiences have been [17].…”
Section: Stigma and Marital Statusmentioning
confidence: 99%
“…These result in various social and medical repercussions, increase the complexity of managing the disease. Access to HIV screening services and early medical treatment is often delayed [4][5][6][7], and PLWHA's opportunities to social support networks and positive interactions with other individuals are limited [8,9]. Moreover, stigma perceived by PLWHA often leads to social isolation and internalized shame, thereby increasing their vulnerability to psychopathology [2,[10][11][12], which may interfere with medication adherence and compromise their health status and quality of life [3,13,14].…”
Section: Introductionmentioning
confidence: 99%